A Guide to the Design of Occupational Safety and Health Training for Immigrant, Latino/a Dairy Workers - Menger, Lauren M.; Rosecrance, John; Stallones, Lorann; Roman-Muniz, Ivette Noami (Frontiers in Public Health, 2016)
Industrialized dairy production in the U.S. relies on an immigrant, primarily Latino/a, workforce to meet greater production demands. Given the high rates of injuries and illnesses on U.S. dairies, there is pressing need to develop culturally appropriate training to promote safe practices among immigrant, Latino/a dairy workers. To date, there have been few published research articles or guidelines specific to developing effective occupational safety and health (OSH) training for immigrant, Latino/a workers in the dairy industry. Literature relevant to safety training for immigrant workers in agriculture and other high-risk industries (e.g., construction) was examined to identify promising approaches. The aim of this paper is to provide a practical guide for researchers and practitioners involved in the design and implementation of effective OSH training programs for immigrant, Latino/a workers in the dairy industry. The search was restricted to peer-reviewed academic journals and guidelines published between 1980 and 2015 by universities or extension programs, written in English, and related to health and safety training among immigrant, Latino/a workers within agriculture and other high-risk industries. Relevant recommendations regarding effective training transfer were also included from literature in the field of industrial-organizational psychology. A total of 97 articles were identified, of which 65 met the inclusion criteria and made a unique and significant contribution. The review revealed a number of promising strategies for how to effectively tailor health and safety training for immigrant, Latino/a workers in the dairy industry grouped under five main themes: 1) understanding and involving workers; 2) training content and materials; 3) training methods, 4) maximizing worker engagement; and 5) program evaluation. The identification of best practices in the design and implementation of training programs for immigrant, Latino/a workers within agriculture and other high-risk industries can inform the development of more effective and sustainable health and safety training for immigrant, Latino/a dairy workers in the U.S. and other countries.